MENENTUKAN PREDIKSI REKOMENDASI BIMBINGAN KONSELING SISWA SEKOLAH MENENGAH KEJURUAN MENGGUNAKAN K-NEAREST NEIGHBOR - Wildani Eko Nugroho; Heru Saputro (Journal of Information System and Computer, 2022)
The problem of counseling guidance is one of the problems found in schools which is one thing that is difficult to predict. Accurate predictions are needed to support decision making for those who have policy in making decisions. One of the things that can be done to make predictions in providing guidance and counseling recommendations is to use the K-Nearest Neighbor method. Of the 388 students in the school, tests or experiments can be carried out using the K-Nearest Neighbor algorithm method. The results obtained from the experiment were 96.40% with 362 students who did not have to do counseling guidance, and 62 students who had to do counseling guidance. From the experimental results, it is hoped that the quality of the education system being carried out is expected to be further improved because it will affect the quality of the school.